Effect of Neuromuscular Control on Pain among Patients with Osteoarthritis in Indonesia: Quasi-Experiment - Warsono Warsono; Faradisa Yuanita Fahmi; Anita Rachmawati; Satriya Pranata (Babcock University Medical Journal)
Objective: to analyse neuromuscular control's effect on pain among osteoarthritis patients.